Analisis Parkir Perumda Pasar Pakuan Jaya - Rifaldi, Reza; Rulhendri; Chayati, Nurul (Journal of Applied Civil Engineering and Infrastructure Technology, 2025)
The research aims to manage parking facilities so that there are no more vehicles parking in the area outside the Pakuan Jaya Market Perumda market; therefore, vehicles that park in the area outside the Pakuan Jaya Market Perumda market parking facility are placed in the Pakuan Jaya Market Perumda parking facility area so as not to reduce the road capacity. In this study, using the SRP method of characteristics (Volume, Accumulation, Duration, Turnover, Index), the performance management of paid parking is examined. Data collection was carried out by the survey method, with a time of 12 hours and running for sixteen days, with the data taken being the data of vehicle entry and exit hours to determine the characteristics of parking. The results of this study comprise the calculation of characteristics, including the maximum parking cumulation of 199 vehicles, which occurred on Friday, 12 April 2024 with a vehicle volume of 176 vehicles, and the maximum parking duration for At noon on the peak day, Thursday 4 April 2024, for sixteen days, the highest turnover of motorcycle parking at Perumda Pasar Pakuan Jaya Bogor City was observed at 30.03%. The maximum parking index reached 33.96%, indicating that the parking performance was relatively poor. However, the motorcycle parking capacity at Perumda Pasar Pakuan Jaya Kota Bogor was sufficient to meet the existing parking demand due to the capacity of the existing parking spaces. This was indicated by the parking index, which is less than 100%.